Bilateral Multiple Level Lateral Meningocoele - Kumar, B. E. Panil (Medknow Publications & Media Pvt Ltd, 2013)
Lateral meningocoele is a very rare disorder characterized by extensions of the dura and arachnoid through an enlarged neural foramen. We report a case of a 23-year-old female with deformity of spine who presented with low back pain and no neurological deficits. A whole spine magnetic resonance imaging showed multiple well-defined cystic masses involving dorsal, lumbar, and sacral spinal levels bilaterally, with dural ectasia and neural foraminal widening suggestive of bilateral multiple level lateral meningocoele. The patient is being managed conservatively and is on regular follow-up.